(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Isolated sleep paralysis (disturbed sleep) is a condition in which a person is in a state of consciousness but is not able to move or speak in the bed even if he wants to. It is a dreadful condition for a person, in which he or she even fears to fall asleep. It can occur with or without being a part of a sleeping disorder named narcolepsy. According to Ayurveda conditions of isolated sleep paralysis occurring during rapid eye movements (REM) phase of sleep can be correlated to Tandra and Manovaha Sroto Dushti in a stressed individual (Alpa Satva Purush). Ayurveda has potential to treat sleep related disorders with the help of Panchkarma procedures namely Shirodhara. In modern medicine treatment of conditions like isolated sleep paralysis mainly depends on use of antidepressant and sedative medicines which has many side effects. In this case an effort has been made to treat a young male of 21 years with symptoms of helplessness or muscle atonia during initiation of his sleep hours with heaviness in chest, difficulty in respiration and choking sensation for past 2 years. Treatment given is Shirodhara for a period of 15 days with Brahmi oil and tablet Sarpangdha as an internal medicine. The result shows positive response by decreased frequency of attacks, time duration and other symptoms along with improvement in quality of life.